Return to Sports After High Tibial Osteotomy Using the Opening Wedge Technique - Nicolini, Alexandre Pedro; Christiano, Eduardo Suñe; Abdalla, Rene Jorge; Cohen, Moises; de Carvalho, Rogério Teixeira (Revista Brasileira de Ortopedia, 2020)
Objective The present paper evaluates the resuming of physical activities by young, active patients who practiced some sport modality and underwent a high tibial osteotomy (HTO) using the opening wedge technique.Methods A total of 12 patients submitted to HTO using the opening wedge technique were prospectively analyzed. All patients were not playing sports at that time. Pre- and postoperative Lysholm and International Knee Documentation Committee (IKDC) scores, visual analog scale for pain and performance level were compared. The average follow-up time was of 12 months.Results One patient resumed sporting activities at a performance level significantly lower compared to the preoperative level, while eight patients returned at a slightly below level, two returned at the same level and one patient returned at a higher level in comparison with the preoperative period.Conclusion For isolated medial osteoarthrosis treatment, HTO using the opening wedge technique has favorable clinical and functional results, allowing patients to resume their sporting activities.
Keywords: osteoarthrosis; osteotomy; sports; tibia